Abundance and Distribution Pattern of Macroinvertebrates at Watu Lumbung Beach, Gunungkidul, Yogyakarta - Rahmawati, Yunita Fera; Putri, Rizka apriani; Prakasa, Tatag Bagus Putra; Aedhiningtyas, Chrisshinta Iris; Hermawan, Lisa Agustina (Biosfer: Jurnal Tadris Biologi, 2024)
This research aimed to determine the abundance and distribution of macroinvertebrates at Watu Lumbung Beach, Gunungkidul, Yogyakarta. The study was conducted in May 2022 using the quadratic transect method with a 1x1 m plot. Sampling was carried out at two randomly selected stations. The first station was located 50 meters from the Watu Lumbung reef, while the second station was 250 meters away, resulting in a 200-meter distance between the two stations. Data analysis involved calculating the Shannon-Weiner diversity index (H'). This study identified 16 species of macroinvertebrates at Watu Lumbung Beach, classified into 13 families and nine classes: Polychaeta, Malacostraca, Anthozoa, Echinoidea, Ophiuridae, Gastropoda, Polyplacophora, Pilidiophora, and Demospongia. The family Ophiocomidae, specifically Ophiocoma erinaceus and Ophiocoma scolopendrina, was the most abundant at both stations. The diversity level was moderate, with a Shannon-Weiner index value of 1.94.ABSTRAK: Penelitian ini bertujuan untuk mengetahui kelimpahan dan sebaran makroinvertebrata di Pantai Watu Lumbung, Gunungkidul, Yogyakarta. Penelitian ini dilaksanakan pada bulan Mei 2022 dengan metode transek kuadrat dengan ukuran 1x1m. Pengambilan sampel dilakukan pada dua stasiun yang ditentukan secara acak. Stasiun pertama terletak di dekat karang Watu Lumbung dengan jarak 50 meter, sedangkan stasiun kedua berjarak 250 meter dari karang, sehingga jarak antar stasiun adalah 200 meter. Analisis data dilakukan dengan menghitung indeks keanekaragaman Shannon-Wiener (H’). Pada penelitian kali ini diketahui kelimpahan makroinvertebrata di Pantai Watu Lumbung berjumlah 16 spesies, dikelompokkan dalam 13 famili, dan diklasifikasikan dalam sembilan kelas (Polychaeta, Malacostraca, Anthozoa, Echinoidea, Ophiuridae, Gastropoda, Polyplacophora, Pilidiophora dan Demospongia). Famili Ophiocomidae (Ophiocoma erinaceus dan Ophiocoma scolopendrina) merupakan spesies yang paling melimpah di kedua stasiun pengamatan. Keberagaman tersebut termasuk dalam kategori sedang dengan nilai 1,94.